The informational “cosplay journey” of Star Wars cosplayers in the context of a Facebook group - Vardell, Emily; Thomas, Paul; Wang, Ting (Information Research an international electronic journal, 2023)
Introduction. Research on personal information practices has increased in recent decades. Building on this current of thought, the present study explores information practices in the context of serious leisure, looking specifically at the Rey Cosplay Community Facebook group, an online community of Star Wars cosplayers. The work discusses how these fans seek, organize, and share relevant information during the process of making costumes. Method. This study used participant observation and semi-structured interviews to investigate information behaviours, including information seeking, organization, use, and sharing, of seventeen members in the Rey Cosplay Community with a purposive sampling strategy. Analysis. The researchers transcribed and jointly coded the collected data with an open coding scheme to identify themes that emerged from the data. Results. The cosplayers used a myriad of tools to seek, organize, and share information about costume making. Participants identified that their information practices had evolved over time, and they shared sophisticated strategies for sharing work-in-progress photos and updates as well as methods for organizing information for later use. Conclusion. There are a variety of information practices used when making a costume. Participants often seek and acquire relevant information on online platforms and use a combination of traditional physical tools and modern electronic tools to organize information. They also display a rich culture of sharing information when responding to other fans’ information needs. The overall structure that these information practices take can be neatly articulated as a sort of informational “cosplay journey”.